Upaya Guru Tahfidz Dalam Meningkatkan Hafalan Al-Qur’an Pada Santri Di PPTQ Muhammadiyah Darul Hikmah Masaran Sragen - Mulathif, Miftahul Huda Nurrokhim; Salim, Hakimuddin (Jayapangus Press, 2025)
This study aims toanalyze the efforts of Tahfidz teachers in improving the memorization of the Qur'anby students at the Muhammadiyah Darul Hikmah Masaran Islamic Boarding SchoolSragen and to identify the supporting and inhibiting factors in theTahfiz learning process. The research used a descriptive qualitative approachwith data collection techniques through participatory observation, in-depth interviews, and documentation. Data analysis was conducted thematically through the stages of reduction, data presentation, and conclusion drawing. The results of the studyshow that the improvement of students' memorization is carried out through the Talaqqi, Murajaah, and Ummi methods, the setting of memorization targets, the provision ofmotivation and rewards, the application of educational punishments, and routine evaluations inscheduled halaqah. Supporting factors for success include a conducive pesantren environment, intensive mentoring, an ideal caregiver-to-student ratio, innovationby young teachers, uniformity of mushaf, and the use of teaching aids. Meanwhile, hindering factors include differences in the abilities and backgrounds of santri as well astime management limitations. This study emphasizes the importance of targeted teaching strategies and a supportive learning environment tooptimize students' Quran memorization outcomes.